Alternative control of coffee diseases - Carvalho, Vicente Luiz; Cunha, Rodrigo Luz da; Silva, Nathan Resende Naves (Coffee Science - ISSN 1984-3909, 2012)
The Rust and Brown-eye-spot are the principle diseases of this crop. The control of these diseases is done by agrochemicals and most of the time is used indiscriminately. While at the same time consumers are demanding produce free of agrochemicals. Based on these facts, this paper aimed to test natural and/or alternative products to control these coffee diseases. These products are less toxic to humans and the environment, are economically viable for the producer and consequently improve the final product quality. The experiment was conducted in São Sebastião do Paraíso Experimental Farm, containing 8 treatments: 1 – Alcoholic extract of tomilho 2%; 2 – Rocksill 2%; 3 – Cupper (cupper hydroxide) 0,58% and Rocksil 1%; 4 –Aqueous extract of coffee husk 3%; 5 – Potassium nitrate 1%; 6 – Calcium nitrate 0,5% + Biotec; 8 – Potassium Silicate 0,66%; 9 – Viça coffee 0,83%; 10 – Control. The results showed that the Vica-cafe was the most effective in controlling rust, reducing more than 60% AUDPC and the defoliation 38% in the second year, when compared with the control. The intercalated application of cupric and silicate clay reduced the incidence of Brown-eye-spot by 57% and 75% AUDPC respectively in the first and second years evaluated and defoliation by more than 40% when compared to the control.